Development of minimal fermentation media supplementation for ethanol production using two Saccharomyces cerevisiae strains. Issue 9 (2nd May 2016) - Tropea, Alessia; Wilson, David; Cicero, Nicola; Potortì, Angela G.; La Torre, Giovanna L.; Dugo, Giacomo; Richardson, David; Waldron, Keith W.
Abstract: Ethanol production by fermentation is strongly dependent on media composition. Specific nutrients, such as trace elements, vitamins and nitrogen will affect the physiological state and, consequently, the fermentation performance of the micro-organism employed. The purpose of this study has been to assess the highest ethanol production by a minimal medium, instead of the more complex nutrients supplementation used during alcoholic fermentation. All fermentation tests were carried out using a microwell plate reader to monitor the processes. Two Saccharomyces cerevisiae strains (NCYC 2826 and NCYC 3445) were tested using three nitrogen sources, supplied with different vitamin and salts. The results show that solutions made of urea phosphate, KCl, MgSO4 ·7H2 O, Ca-panthothenate, biotin allowed an ethanol yield of 22.9 and 23.4 g/L for strain NCYC 2826 and NCYC 3445, respectively, representing 90 and 92% of the theoretical yield. All tests were carried out using glucose as common reference carbon source. Abstract :